2018
DOI: 10.1186/s11658-018-0088-y
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between the Warburg effect, redox regulation and autophagy induction in tumourigenesis

Abstract: Tumourigenic tissue uses modified metabolic signalling pathways in order to support hyperproliferation and survival. Cancer-associated aerobic glycolysis resulting in lactic acid production was described nearly 100 years ago. Furthermore, increased reactive oxygen species (ROS) and lactate quantities increase metabolic, survival and proliferation signalling, resulting in increased tumourigenesis. In order to maintain redox balance, the cell possesses innate antioxidant defence systems such as superoxide dismut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 135 publications
0
71
0
2
Order By: Relevance
“…Literature has also recently described molecular cross-talk between the Warburg effect, redox homeostasis, and autophagy induction-all processes proposed as potential drivers of AD (Tonnies & Trushina, 2017;Uddin et al, 2018;Vlassenko & Raichle, 2015). To the extent that this crosstalk is mediated by known pathways such as phosphatidylinositol-3-kinase/ protein kinase B (PI3K/Akt) activation, mammalian target of rapamycin (mTOR) signal transduction, and mitogen-activated protein kinase (MAPK) activity (Gwangwa, Joubert, & Visagie, 2018), their role in integrating pro-survival versus pro-apoptotic signaling in DS-AD should be further evaluated, ideally in neural tissue.…”
Section: Lactic Acid Production and Oxidative Stress: Complementarymentioning
confidence: 99%
“…Literature has also recently described molecular cross-talk between the Warburg effect, redox homeostasis, and autophagy induction-all processes proposed as potential drivers of AD (Tonnies & Trushina, 2017;Uddin et al, 2018;Vlassenko & Raichle, 2015). To the extent that this crosstalk is mediated by known pathways such as phosphatidylinositol-3-kinase/ protein kinase B (PI3K/Akt) activation, mammalian target of rapamycin (mTOR) signal transduction, and mitogen-activated protein kinase (MAPK) activity (Gwangwa, Joubert, & Visagie, 2018), their role in integrating pro-survival versus pro-apoptotic signaling in DS-AD should be further evaluated, ideally in neural tissue.…”
Section: Lactic Acid Production and Oxidative Stress: Complementarymentioning
confidence: 99%
“…This metabolic re-programming in cancer was famously discovered by Warburg and Cori in the 1920s [8,9] and has been suggested as a cancer cell means to evade toxic levels of ROS production. However, maintenance of this Warburg effect requires higher glucose uptake and elevated metabolic activity making tumour cells nevertheless heavily reliant on the antioxidant machinery and maybe even more susceptible to oxidative stress [10,11]. Therefore, highly proliferative cancer cells are known to require handling of elevated cellular ROS levels in order to successfully establish tumours [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies have shown that autophagy through Glut-1 translocation affects glucose uptake of cancer cells [19][20][21][22][23]. In comparison with normal cells, cancer cells preferentially produce energy by glycolysis in anaerobic environments [4]. The energy supply of cancer cells in hypoxic environments is related to the high-level expression of Glut-1 and autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Laryngeal squamous cell carcinoma (LSCC), which is related to many risk factors, including smoking, drinking alcohol, and laryngeal reflux, is one of the most common malignant tumors occurring in the head and neck [1]. Some studies have demonstrated that autophagy and glucose metabolism play important roles in the occurrence and development of cancer cells [2][3][4][5]. However, the mechanisms underlying autophagy and glucose metabolism in the process of LSCC remain unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation